Kajian Pengaruh COVID-19 Terhadap Stabilitas Ekonomi Kota Mojokerto Bulan Januari - Maret 2020 - Penangsang, Parikesit; Studiviany, Pramita; Wiwoho, Bambang (JEB17 : Jurnal Ekonomi dan Bisnis, 2020)
The 2019-2020 Corona virus pandemic (Covid-19) is the 2019 corona virus spread throughout the world. The Covid-19 outbreak was first detected in Wuhan City, China in December 2019, and was designated as a pandemic by the World Health Organization (WHO) on March 11, 2020. The Covid-19 outbreak resulted in Indonesia, the spread of the Corona virus not only disrupted human health, this virus also disturbs the health of the economy throughout the world.Indonesia's economic growth is expected to fall to 2.3 percent, even reaching negative 0.4 percent. The rupiah is currently touching Rp. 16,000, and has an impact on the wheels of the economy in Indonesia. Many residents of the city of Mojokerto are starting to struggle economically, buying daily necessities, is this the people's purchasing power? Public purchasing power is usually associated with rising prices in general, namely "inflation".The calculation of the Mojokerto city inflation is calculated based on the CPI calculation, the average monthly inflation from January - March 2020 for 28 types of staples, amounting to 0.13%. This inflation is categorized as a type of mild inflation, namely inflation which is still not so disturbing economic conditions. There are 3 types of staples slightly affected by inflation, namely cayenne pepper 0.96%, onion 1.83% and tomatoes 0.98% greater than the average mild inflation of 0.83%.Mojokerto city inflation is in Voletile Food by 0.21% not Administered Inflation, so that the inflation of basic needs is not affected by Covid-19, but there are government regulations to reduce the spread of Covid-19 in humans which can result in death, resulting in the community becoming panic buying , i.e. assumes that there will be an increase in the price of goods and the number of goods in the market decreases. Keywords: Inflation, People's Purchasing Power and Covid 19